Introducing an archival collecting model for the records created by South African Portuguese community organisations. Issue 3 (1st September 2016) - Rodrigues, Antonio
Abstract: This article is based on a study which aimed at broadening archival representation by investigating how to bring the contemporary history of the South African Portuguese community into the country's archival heritage. To achieve this aim, the study sought to develop an archival collecting model for the records generated by Portuguese community-based organisations, since these materials are deemed an important source for preserving the social history, memories and experiences of an under-documented group, such as the Portuguese in South Africa. National and international sources were analysed and reviewed, and an empirical investigation to examine the Portuguese community organisations was conducted, in order to gain an understanding of the most effective strategies for collecting, managing and preserving these records. This article therefore proposes an archival collecting model for the records generated by South African Portuguese community-based organisations which demonstrates the processes, resources and other factors that are necessary to establish and sustain an archival collecting initiative for the Portuguese community in South Africa. It is hoped that, in addition to benefitting the Portuguese community, the model will also benefit other underdocumented communities in South Africa interested in preserving their histories and experiences.